2018
DOI: 10.1186/s12943-018-0898-6
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-derived exosomes induce N2 polarization of neutrophils to promote gastric cancer cell migration

Abstract: BackgroundExosomes are extracellular vesicles that mediate cellular communication in health and diseases. Neutrophils could be polarized to a pro-tumor phenotype by tumor. The function of tumor-derived exosomes in neutrophil regulation remains unclear.MethodsWe investigated the effects of gastric cancer cell-derived exosomes (GC-Ex) on the pro-tumor activation of neutrophils and elucidated the underlying mechanisms.ResultsGC-Ex prolonged neutrophil survival and induced expression of inflammatory factors in neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
207
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 243 publications
(213 citation statements)
references
References 56 publications
5
207
0
1
Order By: Relevance
“…In addition to TAM, fibroblasts, dendritic cells, epithelial cells, neutrophils, and lymphocytes can also be tamed by tumor cells and promote a tumor malignant environment. [53][54][55][56][57][58] It has been reported that dendritic cells, fibroblasts, and epithelial cells tamed by cancer cells secrete CCL2. [55][56][57][58]…”
Section: Discussionmentioning
confidence: 99%
“…In addition to TAM, fibroblasts, dendritic cells, epithelial cells, neutrophils, and lymphocytes can also be tamed by tumor cells and promote a tumor malignant environment. [53][54][55][56][57][58] It has been reported that dendritic cells, fibroblasts, and epithelial cells tamed by cancer cells secrete CCL2. [55][56][57][58]…”
Section: Discussionmentioning
confidence: 99%
“…Mantovani et al (20) showed that tumor-associated inflammation is characterized by the swelling of inflammatory cells and the production and release of inflammatory factors in tumor tissues. Inflammatory cells and immune cells, such as neutrophils, lymphocytes, and monocytes, in the peripheral blood of patients with tumor-associated inflammation are considered to be important factors leading to tumor development, invasion and metastasis (21)(22)(23)(24). Existing studies have shown that the NLR and LMR play important roles in determining the prognosis of cancer patients (25-27).…”
Section: Discussionmentioning
confidence: 99%
“…More and more evidences showed that neutrophils played an important role in tumor tissue infiltration to promoting the growth, invasion, angiogenesis and metastasis of various types of cancer [19,20]. In addition, studies showed that exosomes as a novel mechanism of intercellular communication, could lead to the exchange of genetic information and reprogramming of recipient cells and transport various biomolecules, such as proteins, messenger RNAs (mRNAs), microRNAs (miRNAs), and long non-coding RNAs (lncRNAs) [21,22]. Recent studies showed that exosomes play multiple roles in promoting tumor growth, metastasis and drug resistance.…”
Section: Discussionmentioning
confidence: 99%